The Application Of The Presumption Of Innocence By Judges In Indonesia’s Criminal Justice Process: A Challenge - Mula Warman Harahap; I Nyoman Nurjaya; Faizin Sulistio (CV. AFDIFAL MAJU BERKAH, 2026)
The presumption of innocence is a cornerstone of criminal procedure, requiring that every suspect, arrestee, or defendant be treated as not guilty until a court decision has obtained permanent legal force. Its application by judges in Indonesia, however, faces three interrelated challenges. First, a defendant’s status as a recidivist often triggers judicial bias, shifting a judge’s perspective from “presumed innocent” toward “presumed guilty” before the evidentiary process concludes. Second, the guilty-plea mechanism introduced under the 2025 Criminal Procedure Code creates conceptual tension with the presumption, since it allows a defendant’s own admission to substitute, in practice, for adversarially tested proof. Third, intense media coverage and public opinion risk producing a “trial by the press” that undermines judicial independence and objectivity. Using a normative juridical approach, this study argues that strengthening judicial moral integrity, adopting firmer ethical guidelines, and reinforcing safeguards for judicial independence are necessary so that the presumption of innocence is genuinely realized in Indonesian criminal justice practice.